Pengaruh Teknik Restrukturisasi Kognitif Terhadap Penurunan Kecemasan Pada Mahasiswa Tingkat Akhir Dalam Menyusun Penelitian Di Sekolah Tinggi Ilmu Kesehatan Indonesia Maju Jakarta - Yani, Izma Febry; Sancka Stella G. Sihura; Lannasari, Lannasari (An-Najat, 2025)
Final year students in writing thesis will generally experience many problems, one of the factors that hinders students in writing thesis is anxiety. Anxiety is an unpleasant feeling as a general reaction to the inability to cope with a problem. Cognitive restructuring technique is a cognitive therapy to help identify, evaluate and modify thoughts and emotions that are useful for reducing anxiety levels in final year students in writing thesis. This study aims to determine the effect of restructuring techniques on the level of anxiety in final year students in writing thesis. The method in this study is a pre-experimental quantitative research with a one group pretest-posttest design model. The population in this study were final year students in writing a thesis at the Advanced Indonesian School of Health, which amounted to 20 respondents. The sampling technique used is probability sampling, namely simple random sampling. Collecting data using the standard HAM-A or HARS questionnaire which consists of 14 questions that are given before and after being treated with cognitive restructuring techniques. The results of the analysis test used the Wilcoxon Signed Rank-Test.Based on the results of statistical tests obtained p-value 0.000 < 0.05 which indicates that there is an effect of cognitive restructuring techniques on reducing anxiety in final year students in writing thesis.